Semiótica, publicidad y jóvenes: Discriminación de género en una marca de telefonía celular - Ortíz, María Gabriela (2018)
In this investigation we elaborate a semiotic analysis of advertisement addressed to young Ecuadorean people by the cellular telephone company Tuenti. Afterwards, we perform a perception study using the Focus Group technique. The objective is to find out the perception that young people have regarding the messages transmitted in the advertisements y the aforementioned brand, and whether thy normalize gender discrimination and machismo. The results evidence that the analyzed adverts use images of women and reproduce stereotypes which are perceived as discriminatory or machistas. © 2018, Universidad del Zulia. All rights reserved.